Inequality and poverty in rural China - Chuliang Luo; Terry Sicular (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Chapter from: 'Rising Inequality in China: Challenge to a Harmonious Society', edited by Shi Li, Hiroshi Sato and Terry Sicular.
Keywords: 330; Soziale Ungleichheit; Ländliche Armut; China